Baroque persistence - Báez, Rolando; Vargas, Emilio (Base Diseño e Innovación, 2015)
Trying to establish a crossing between contemporary jewelry production and Chilean cultural heritage, Joya Brava created a collection and a collective exhibition. More than thirty goldsmiths developed pieces inspired in conceptual approaches and thoughts on the Latin American baroque movement and its profound influence in Chilean popular culture.